STRATEGI INOVASI PENGEMBANGAN UNTUK MENINGKATKAN DAYA SAING DI PASAR - Tania, Wynne Dea Aprillia Tania; Sufiyati (Jurnal Serina Abdimas, 2024)
The implementation of this PKM activity aims to analyze the innovation strategies employed by Fizzyfun in selling soda products to enhance market competitiveness. The approach used is qualitative, employing a case study method. The PKM activity focuses on applying the 4P marketing mix theory (Product, Price, Place, Promotion). Innovation in product, pricing, distribution, and promotion serves as the key elements in developing a marketing strategy to increase competitiveness in the market. The results show that product innovation, including the introduction of new, healthier flavors, the use of natural ingredients, and eco-friendly packaging, successfully attracted consumer attention, especially from health-conscious and environmentally-aware customers. Fizzyfun's price penetration strategy also succeeded in expanding its market segment, particularly among price-sensitive consumers. In terms of distribution, leveraging e-commerce platforms and partnerships with online food delivery services provided broader accessibility to consumers. Additionally, promotional campaigns through digital media and influencer engagement boosted brand awareness and consumer loyalty toward the product. In conclusion, innovation within the 4P marketing mix significantly impacted Fizzyfun's competitiveness in a crowded market. Integrated innovations in product, pricing, distribution, and promotion helped strengthen the product's market position and improve overall sales performance. ABSTRAKPelaksanaan kegiatan PKM ini bertujuan untuk menganalisis strategi inovasi pengembangan yang diterapkan oleh Fizzyfun dalam menjual produk minuman soda untuk meningkatkan daya saing di pasar. Metode pendekatan yang digunakan adalah kualitatif dengan metode studi kasus. Pelaksanaan kegiatan PKM ini berfokus pada penerapan teori bauran pemasaran 4P (Product, Price, Place, Promotion). Inovasi produk, harga, distribusi, dan promosi menjadi elemen utama dalam pengembangan strategi pemasaran untuk meningkatkan daya saing di pasar. Hasil dari penerapan teori ini menunjukkan bahwa inovasi produk melalui pengenalan varian rasa baru yang lebih sehat, penggunaan bahan alami, dan kemasan yang ramah lingkungan berhasil menarik perhatian konsumen terutama yang peduli dengan kesehatan dan keberlanjutan. Strategi penetrasi harga yang diterapkan Fizzyfun juga berhasil memperluas segmen pasar, terutama di kalangan konsumen yang sensitif terhadap harga. Di sisi distribusi, pemanfaatan platform e-commerce dan kemitraan dengan layanan pengiriman makanan online memberikan aksesibilitas yang lebih luas kepada konsumen. Selain itu, kampanye promosi melalui media digital dan keterlibatan influencer berhasil meningkatkan kesadaran merek dan loyalitas konsumen terhadap produk. Kesimpulannya, inovasi dalam bauran pemasaran 4P memberikan dampak yang cukup signifikan terhadap peningkatan daya saing Fizzyfun di pasar yang kompetitif. Inovasi yang terintegrasi dalam produk, harga, distribusi, dan promosi membantu memperkuat posisi produk di pasar dan meningkatkan performa penjualan secara keseluruhan